Prevalence and Mean Intensity of Nematode Parasites in Anurans of the Genus Sclerophrys in Burkina Faso (West Africa) - Soubeiga, Patricia; Boungou, Magloire; Thiombiano, Noel Gabiliga; Chabi, Adechegoun Meschac Bertrand; Zougouri, Nakoula Emile; Ouédraogo, Nazeguenimba Armel; Bagayan, Mohamed; Sinare, Yamba (European Scientific Journal, ESJ, 2026)
A study aimed at better understanding parasitic infections was conducted on nematode parasites infecting anurans of the genus Sclerophrys between June 2022 and November 2023 in the provinces of Ganzourgou, Kadiogo, and Houet in order to preserve them. To do this, anurans were collected at night using the VAES method (Visual and Acoustic Encounter Survey), then dissected in order to search for nematodes. The results indicate that 743 anurans were collected. These anurans belong to four species: Sclerophrys maculata, S. regularis, S. pentoni and Sclerophrys xeros. Of the 743 anaintensities examined, 669 individuals were infected with nematodes, representing an overall prevalence of 90.04%. Nine species of nematodes were identified: Amplicaecum pesteri, Cosmocerca ornata, Oswaldocruzia sp., Physaloptera sp., Rhabdias africanus, Rhabdias sp., Cosmocercella sp., Cosmocercoides sp. and Aplectana sp. The most widespread species was Cosmocercoides sp. (58.95%), while Cosmocerca ornata was the least prevalent (0.26%). No significant variation was observed in prevalence in relation to the infected organ (p = 0.7128 > 0.05), sex (p-value = 0.06031 > 0.05) and season (p-value = 0.2365 > 0.05). This study provides significant information on the population of Sclerophrys anurans and their nematode parasites. The high overall prevalence in these toads of the genus Sclerophrys reveals that these populations could be threatened by mortality induced by this high parasite load. In addition, the parasite load was notably higher in environments with increased pollution due to the use of chemical fertilizers. Therefore, the preservation of these organisms would require the adoption of sustainable agricultural practices.